High serum levels of BAFF, APRIL, and TACI in common variable immunodeficiency - Knight, Adina K (Clinical immunology (Orlando, Fla.), 2007)
Common variable immunodeficiency (CVID) is characterized by low levels of immune globulins and lack of antibody. Mutations in transmembrane activator and calcium-modulating cyclophilin ligand (TACI), are found in 8-10%, associated with autoimmunity and splenomegaly. Some patients with mutations had increased serum levels of TACI. Because of this, and the prevalence of autoimmunity, splenomegaly, and lymphadenopathy, we quantitated levels of TACI ligands, a proliferation inducing ligand (APRIL) and B cell activating factor (BAFF) and TACI in serum of 77 patients. CVID subjects had markedly increased serum levels of BAFF (p<0.0001), APRIL (p<0.0001), and TACI (p=0.001) but there was no relationship between levels and autoimmunity, lymphadenopathy, splenomegaly, B cell numbers, or mutations in TACI. Peripheral blood mononuclear cells of CVID subjects had increased levels of BAFF mRNA. We conclude that increased constitutive production and/or underlying immuno-regulatory or inflammatory conditions lead to enhanced release of ligands; however, the biological result remains unclear